Consumption Survey of Justicia Galeopsis T. Anderson Ex C.B. Clarke (Acanthaceae) a Wild Food Plant in Côte d’Ivoire (West Africa) - Ahou Leticia Loukou; Koua Herve Kouakou; Adouko Edith Agbo; Kouakou Brou (European Scientific Journal, ESJ, 2018)
The aim of this study was to evaluate the level of knowledge and consumption of Justicia galeopsis, a wild food plant, in Abengourou (Côte d’Ivoire). A survey of food consumption has been conducted among the populations and 100 persons have been interviewed. The data revealed that they all have already consumed J. galeopsis leaves. The main reasons of J. galeopsisleaves consumption refer to nutritional value and flavor. There were always cooking before eating and associated mainly with groundnuts (95%) or gumbo (5%). Twenty-seven percent of consumers every day eat J. galeopsis leaves against 64% who consume once or twice a week, 6% twice a month, 3% occasionally. 6% the populations collected these leaves in the market against 94% who obtained them from their field which is far from the village. Although the fields were far from the village, 74% of population prepares J. galeopsis just after the collect without conservation. The cooking time of leaves associated with peanuts or okra is estimated by 41% of the households at 30 minutes. Five percent prepared them during 45 minutes and 22% during one (1) hour. This study reveals that J. galeopsis is a famous plant in Abengourou. Its leaves are greatly appreciated by all populations studied.